The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1084/jem.173.1.89
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 4 expressed in situ selectively alters thymocyte development.

Abstract: SummaryUsing a transgenic mouse model we show that increased intrathymic expression of interleukin 4 (IL4) significantly perturbs the development of thymocytes. Transgenic double-positive (CD4+CD8+) thymocytes, which are present in dramatically reduced numbers, exhibit increased T cell receptor (TCR) expression and increased mobilization ofcalcium mediated by these receptors. In contrast, transgenic single-positive (CD4+CD8 -and CD4 -CD8+) thymocytes and peripheral T cells exhibit decreased TCRmediated calcium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
2

Year Published

1992
1992
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 67 publications
4
32
0
2
Order By: Relevance
“…Constructs using the insulin promoter may direct expression of the transgene not only to pancreatic J3 cells but also to the thymus (24,25). Furthermore, it has been shown that IL-4, when selectively overexpressed in the thymus oftransgenic mice, significantly alters thymocyte development and thymus architecture (19). To address possible transgene expression in the thymus of NOD-IL-4 mice, IL-4 levels in supernatants from thymocytes after short-term in vitro culture were determined using an ELISA assay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Constructs using the insulin promoter may direct expression of the transgene not only to pancreatic J3 cells but also to the thymus (24,25). Furthermore, it has been shown that IL-4, when selectively overexpressed in the thymus oftransgenic mice, significantly alters thymocyte development and thymus architecture (19). To address possible transgene expression in the thymus of NOD-IL-4 mice, IL-4 levels in supernatants from thymocytes after short-term in vitro culture were determined using an ELISA assay.…”
Section: Resultsmentioning
confidence: 99%
“…Thymocytes from three NOD-IL-4 mice and three nontransgenic littermates were cultured (5 X 106/ml) in RPMI 1640 supplemented with 1 mM NaPyruvate, 2 mM L-glutamine, 0.05 mM 2-ME, 100 U/ml penicillin, 100 ~g/ml streptomycin, and 10% FCS for 24 h (19). Supernatants from islet cells and thymocytes were removed, and IL-4 levels were determined with an ELISA assay using mAb BVD4-1D 11 and biotinylated Ab 11B 11 as capture and detection Abs, respectively (PharMingen, San Diego, CA).…”
Section: Methodsmentioning
confidence: 99%
“…There are both similarities and differences between transgenic Stat6VT mice and transgenic mice overexpressing IL-4 (15,39,69). Transgenic IL-4 had dramatic effects on thymic cellularity and thymocyte maturation, suggesting that an active Stat6 does not mimic all effects of transgenic IL-4 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The LCK-PLZF transgene was constructed by inserting the ∼2KB gene into the LCK vector as described (23). Transgene DNA was injected into fertilized C57BL/6 eggs by the Memorial Sloan-Kettering Cancer Center (MSKCC) Mouse Genetics Core Facility.…”
Section: Micementioning
confidence: 99%